Morphometric Features of Noctiluca scintillans from Jakarta Bay - Radixa Radhya Ramadhan Haryanto; Meutia Samira Ismet; Adriani Sunuddin; Inna Puspa Ayu; Muhammad Izzat Nugraha; Alfaiz Arselan; Kesha Mufthi Java Tanaya; Dea Fauzia Lestari; Dondy Arafat; Nadya Cakasana; Beginer Subhan (Marine Science Department Diponegoro University, 2026)
Noctiluca scintillans is a mixotrophic dinoflagellate commonly associated with eutrophic coastal systems and bloom dynamics. This study aims to characterize the morphometric variability of N. scintillans in Jakarta Bay, a tropical coastal environment strongly influenced by anthropogenic nutrient enrichment, and to evaluate how cellular morphology reflects functional and ecological responses under eutrophic conditions. Plankton samples were collected in February 2024 and analyzed using high-resolution microscopy to quantify key morphometric traits, including cell diameter, biovolume, aspect ratio, surface area-to-volume (SA:V) ratio, and nucleus-to-cytoplasm (N:C) ratio. Differences between red (RNS) and green (GNS) morphotypes were assessed using non-parametric statistical analyses, and preserved measurements were corrected to estimate live cell size. A total of 121 cells were analyzed, with RNS overwhelmingly dominating the population. RNS exhibited significantly larger cell diameter and volume than GNS, while SA:V ratios differed significantly between morphotypes, indicating functional differences in size-related morphology. In contrast, aspect ratio did not differ significantly, suggesting overall conservation of cell shape across morphotypes. Estimated live cell sizes indicate that N. scintillans populations in Jakarta Bay are dominated by relatively small cells compared to those reported from temperate regions. Variability in the N:C ratio further suggests heterogeneity in cellular physiological states within the population. Overall, these findings establish a morphometric baseline for N. scintillans in Jakarta Bay and highlight the value of morphometric traits as integrative indicators of physiological variability and environmental forcing in tropical eutrophic coastal systems.